Lysyl oxidase promotes seminal vesicle atrophy and fibrosis in type-2 diabetes mellitus through TGF-β1 signaling - Yi Yu; Peng-Fei Liu; Ming-Wei Zhan; Yao-Qi Chen; Yu-Qi Lai; Lei Wang; Jun-Jie Wu; Fan Yao; Xue-Qin Chen; Xue-Jun Shang; Ke-Rong Wu (Journal of Translational Medicine)
Abstract Type-2 diabetes mellitus (T2DM) is a complex metabolic disorder that adversely affects various physiological systems, particularly male reproductive health. Research indicates that T2DM increases the risk of retrograde ejaculation, impairing sexual function and fertility. Dysregulation of lysyl oxidase (LOX) has been linked to diabetes-related complications in the male reproductive system. However, its role in seminal vesicle remains unclear. This study investigates LOX’s involvement in diabetes-related seminal vesicle pathology using human and mouse models. We assessed LOX expression in the seminal vesicles of men with T2DM and created a T2DM mouse model to observe changes. Our findings revealed elevated LOX expression in the seminal vesicles of T2DM men, accompanied by epithelial atrophy and fibrosis. Similarly, T2DM mice displayed significant atrophy and fibrosis of the seminal vesicles, correlated with increased LOX levels. Treatment with the LOX inhibitor, β-aminopropionitrile (BANP), significantly improved extracellular matrix remodeling and normalized the architecture of the seminal vesicles. Besides, LOX inhibition led to a significant reduction in T lymphocyte infiltration and apoptosis in the seminal vesicle epithelium of T2DM mice.These results highlight LOX’s critical role in seminal vesicle fibrosis associated with T2DM. Targeting LOX may provide a promising therapeutic strategy to alleviate reproductive complications and preserve reproductive health in men with T2DM. Graphical abstract